Amide C–N bonds activation by A new variant of bifunctional N-heterocyclic carbene - Yuxing Cai; Yuxin Zhao; Kai Tang; Hong Zhang; Xueling Mo; Jiean Chen; Yong Huang (Nature Communications, 2024)
Abstract We report an organocatalyst that combines a triazolium N-heterocyclic carbene (NHC) with a squaramide as a hydrogen-bonding donor (HBD), which can effectively catalyze the atroposelective ring-opening of biaryl lactams via a unique amide C–N bond cleavage mode. The free carbene species attacks the amide carbonyl, forming an axially chiral acyl-azolium intermediate. Various axially chiral biaryl amines can be accessed by this methodology with up to 99% ee and 99% yield. By using mercaptan as a catalyst turnover agent, the resulting thioester synthon can be transformed into several interesting atropisomers. Both control experiments and theoretical calculations reveal the crucial role of the hybrid NHC-HBD skeleton, which activates the amide via H-bonding and brings it spatially close to the carbene centre. This discovery illustrates the potential of the NHC-HBD chimera and demonstrates a complementary strategy for amide bond activation and manipulation.